Contagion of silence behaviors: 방어적 및 체념적 침묵을 중심으로 - Chung, HyunSun; Park, DongGun (Korean Journal of Industrial and Organizational Psychology, 2013)
The present research aimed to investigate the contagion of silence behaviors, and its effects process. 218 respondents who is employed in organizations were surveyed. What were analyzed using structural equation modeling are (1) the contagion of silence behaviors, (2) the casual relationship between two types of silence behaviors(defensive silence, acquiescent silence), and (3) the mediating role of employee’s silence behaviors and acquiescent silence in the process of co-worker’s corresponding behaviors and silence affecting team silence climate and innovative support behaviors. Results indicated that co-worker’s silence behaviors could be contagious and their effects on outcomes were mediated by employee’s silence behaviors. Findings also showed that employee’s defensive silence affected his/her acquiescent silence and its effect on outcomes was mediated by acquiescent silence. From these results, we discussed the theoretical implications of findings, limitations, suggestions for future research in discussion.